2019
DOI: 10.1016/j.celrep.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the In Vivo Role of the Mitochondrial Calcium Uniporter in Brown Fat Bioenergetics

Abstract: Highlights d BAT-specific MCU KO mice have normal body weight and cold tolerance d MCU KO does not impact the gene expression response to acute cold stress in BAT d Cold induces ATF4-dependent integrates stress response in both genotypes d Circulating GDF15 and FGF21 rise in both genotypes in response to cold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 112 publications
(150 reference statements)
0
37
1
Order By: Relevance
“…In vitro and in vivo experiments in this study show that stimulation of Ca 2+ extrusion is indispensable for physiological uncoupled energy expenditure in BA. At first, the results presented here might contrast with a recent report showing in vivo that BAT-MCU KO mice are as cold tolerant as their WT littermates and presenting no basal or adrenergic-stimulated phenotype 20 . However, while BAT function seems to be independent of mitochondrial Ca 2+ uptake by MCU, once it is present in the mitochondrial matrix, Ca 2+ levels must be tightly regulated by NCLX activity to prevent Ca 2+ overload, activation of mPTP and ultimately cell death.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In vitro and in vivo experiments in this study show that stimulation of Ca 2+ extrusion is indispensable for physiological uncoupled energy expenditure in BA. At first, the results presented here might contrast with a recent report showing in vivo that BAT-MCU KO mice are as cold tolerant as their WT littermates and presenting no basal or adrenergic-stimulated phenotype 20 . However, while BAT function seems to be independent of mitochondrial Ca 2+ uptake by MCU, once it is present in the mitochondrial matrix, Ca 2+ levels must be tightly regulated by NCLX activity to prevent Ca 2+ overload, activation of mPTP and ultimately cell death.…”
Section: Discussioncontrasting
confidence: 99%
“…While a rise in mitochondrial calcium has been documented during activation of thermogenesis in BAT, its functional role and regulation has not yet been elucidated. Recently Flicker et al 20 found that mitochondrial Ca 2+ uptake through the mitochondrial calcium uniporter is inconsequential for BAT thermogenic function. However, the role of Ca 2+ extrusion pathway has not been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial Ca 2+ uptake which has been long established as a key mediator of cell survival, metabolism and death needs to be tightly regulated (1,2). The predominant mechanism among ion transporters capable of Ca 2+ uptake into mitochondria is through a highly Ca 2+ -selective ion channel located in the inner membrane called the Mitochondrial Calcium Uniporter (MCU), driven by electrochemical gradient across the inner mitochondrial membrane (IMM) (3)(4)(5)(6). Mitochondrial Calcium Uptake 1 (MICU1), a regulatory subunit that shields mitochondria from Ca 2+ overload, is required for uniporter-mediated Ca 2+ uptake (7).…”
Section: Introductionmentioning
confidence: 99%
“…Given this, it is surprising that zebrafish cone photoreceptors express extremely low levels of MCU 12 . MCU has been widely thought to be the sole route of Ca 2+ entry into mitochondria in eukaryotes, as loss of MCU completely inhibits mitochondrial Ca 2+ uptake in skeletal muscle, liver, heart, brown adipose tissue, and a wide variety of cell lines 15 19 . Despite this, it is possible that certain specialized cell types might not rely solely on MCU for mitochondrial Ca 2+ uptake, since it also has been observed that brain mitochondria lacking MCU expression do not have a complete loss of mitochondrial Ca 2+ uptake 20 .…”
Section: Introductionmentioning
confidence: 99%